Book Review - Umbreen Javaid (Journal of Political Studies, 2012)
The Book titled “Afghanistan and Pakistan Conflict, Extremism and Resistance to Modernity” by Riaz Mohammad Khan has been published by Oxford University Press, Karachi-Pakistan, this book examines the crucial region of Afghanistan and Pakistan. It has dealt with the happenings in Afghanistan and their impact on Pakistan, the two neighboring states with long porous border. Along with this factor there are tribes on both sides of the border which historically have been moving freely on both the sides. Thus there always has been cross border movement.